Negative real permittivity in (Bi0.3Eu0.7)Sr2CaCu2O6.5 ceramic - Kilic, Mehmet; Ozdemir, Zeynep Guven; Karabul, Yasar; Karatas, Ozgul; Cataltepe, Ozden Aslan (ELSEVIER, 2020)
Bi0.3Eu0.7Sr2CaCu2O6.5 was prepared by solid-state reaction method and characterized by Scanning Electron Microscope, X-Ray Fluorescence, X-Ray Diffraction, and electron spin resonance measurements. The frequency dependences of the real and imaginary parts of ac impedance and complex permittivity along with ac conductivity of the sample were studied in 1 Hz-40 MHz range for 296-433 K by an impedance analyzer. The ac impedance analyses of the sample at different temperatures pointed out the possible usage of the material in temperature sensor applications. The negative real permittivity (NRP) was observed at 353 K and the higher temperatures operated. Additionally, it was observed that the cross over frequency, where the real permittivity changes its sign from positive to negative, increases gradually with increasing temperature. The origin of the temperature-induced negative permittivity was discussed in the context of the Drude model and plasma oscillations. Ultimately, Bi0.3Eu0.7Sr2CaCu2O6.5 ceramics can be suggested as source material for NRP.
Keywords: Bi-based perovskite; Rare earth element; Negative real permittivity; Dielectric spectroscopy; STATIC DIELECTRIC-CONSTANT; ELECTRICAL-PROPERTIES; TRANSPORT-PROPERTIES; TEMPERATURE; RELAXATION; WELL; SUPERCONDUCTIVITY; NANOCOMPOSITES; METAMATERIALS; SPECTROSCOPY; Physics